Photo-induced optical bleaching in Ge12Sb25S63 amorphous chalcogenide thin films: effect of 532 nm laser illumination. (12th February 2015) - Naik, Ramakanta; Jena, Shuvendu; Ganesan, R; Sahoo, N K
Abstract: The photo-induced effects of Ge12 Sb25 S63 films illuminated with 532 nm laser light are investigated from transmission spectra measured by FTIR spectroscopy. The material exhibits photo-bleaching (PB) when exposed to band gap light for a prolonged time in a vacuum. The PB is ascribed to structural changes inside the film as well as surface photo-oxidation. The amorphous nature of thin films was detected by x-ray diffraction. The chemical composition of the deposited thin films was examined by energy dispersive x-ray analysis (EDAX). The refractive indices of the films were obtained from the transmission spectra based on an inverse synthesis method and the optical band gaps were derived from optical absorption spectra using the Tauc plot. The dispersion of the refractive index is discussed in terms of the single-oscillator Wemple–DiDomenico model. It was found that the mechanism of the optical absorption follows the rule of the allowed non-direct transition. Raman and x-ray photoelectron spectra (XPS) were measured and decomposed into several peaks that correspond to the different structural units which support the optical changes.